China's rise, Russia's fall: Medium term perspective - Vladimir Popov (Transformation, Integration and Globalization Economic Research (TIGER), 2007)
This chapter is an attempt to interpret recent rapid Chinese growth in a longer term perspective. First, it is argued that recent economic liberalization produced spectacular results (1979-onwards) because reform strategy was very different from the Washington consensus package (gradual rather than instant deregulation of prices, no mass privatization, strong industrial policy, undervaluation of the exchange rate via accumulation of reserves). Besides, the recent Chinese success (1979-onwards) is based on the achievements of the Mao period (1949-76) - strong state institutions, efficient government and increased pool of human capital. Unlike in the former Soviet Union, these achievements were not squandered in China due to gradual rather than shock-therapy type democratization.
Keywords: 330; Wirtschaftswachstum; Systemtransformation; Wirtschaftsreform; Vergleich; China; Russland